Assessment of gps/glonass point positioning in Brazilian regions with distinct ionospheric behavior - Jerez, Gabriel Oliveira [UNESP]; Alves, Daniele Barroca Marra [UNESP] (FapUNIFESP (SciELO), 2020)
Nowadays GPS (Global Positioning System) and GLONASS (GLObal NAvigation Satellite System) are the main systems of GNSS (Global Navigation Satellite Systems), also composed by Galileo and BeiDou. After a long period of degradation, GLONASS was modernized, and its constellation was reestablished in 2011. Considering this new scenario, with GPS and GLONASS full constellations, the interest in the combined use of both systems was renewed. Besides the constellations used, other factors are related to the positioning quality, for instance the ionospheric influence. Several studies have been performed aiming to assess GPS positioning quality as well as the ionospheric influence on it, but concerning GLONASS, there are still several possibilities of investigation. In this context, this research aimed to assess the GPS/GLONASS data point positioning performance considering Brazilian regions with different ionospheric behavior during periods of low and high ionospheric activity. Spatial and time ionospheric influence in the positioning performance were observed. Considering all configurations tested with 30-minute data, the use of GPS/GLONASS data provided better results in 97.35% of the cases when compared to autonomous GPS, the mean improvement was about 60 cm, which corresponds to 30%.
Keywords: GPS/GLONASS; Ionosphere; Positioning